Avaliação do processo de modernização da Biblioteca da Universidade Federal do Tocantins, Campus de Palmas - Brasil, Heloisa dos Santos (2011)
This academic research takes the of moderning process at the library of the University of Tocantins (UFT) on the Campus of Palmas, with it to see the preliminary results of this moderning process are articulated information needs of the academic community. Also understand if there is any relationship between the Institutional Evaluation of the National Assessment of Higher Education (SINAES) and the process of moderning of that library. For this analysis we considered the opinions of members of academic community, so this assessment were not adopted indicators or quality standards previously established. The approach of this evaluative research is interpretive, since of the concept of evaluation of public policies Lejanos (2006), and the mode of assessment is the investigation of this case study. The data were get and analyze resources by triangulation of methods, since they were involved in this study qualitative and quantitative data collected through bibliographical research, participant observation, questionnaires and interviews. We conclude that the process of modernization of the campus library Palmas is considered by its users as significant. However, their investments and actions are conducted in a fragmented way, so the infrastructure for information technology, human resources and the body do not match the needs of users of that library. The design employed in this modernization process is technical and managerial, whose meaning is agility, control and standardization of services of eight libraries of UFT. Note also that this process of modernization were prioritized administrative tasks of the library, so that there was an attempt to focus on meeting the requirements of the evaluation of SINAES, in detriment of the expectations of the academic community. From these data we conclude that this process is consistent with the historical background and the assumptions of the modernization project of the Brazilian higher education, which is based on liberal ideals and emphasizes the technical aspects, the increased efficiency of public administration, productivity, cost effectiveness and so on. It is recommended that the UFT discuss the process of modernization with library users, in order to carry out a systematic planning for continuity, it is also suggested the appointment of an interdisciplinary team to accompany him. Moreover, it is important to effective and expanded student participation in the Steering Committee of the Library System of UFT. So, generally identified that need public policies that coordinate and fund the development of federal university libraries.